De novo phased assembly of the Vitis riparia grape genome - Girollet, Nabil; Rubio, Bernadette; Pierre-Francois, Bert (bioRxiv, 2019)
Grapevine is one of the most important fruit species in the world. In order to better understand genetic basis of traits variation and facilitate the breeding of new genotypes, we sequenced, assembled, and annotated the genome of the American native Vitis riparia, one of the main species used worldwide for rootstock and scion breeding. A total of 164 Gb raw DNA reads were obtained from Vitis riparia resulting in a 225X depth of coverage. We generated a genome assembly of the V. riparia grape de novo using the PacBio long-reads that was phased with the 10x Genomics Chromium linked-reads. At the chromosome level, a 500 Mb genome was generated with a scaffold N50 size of 1 Mb. More than 34% of the whole genome were identified as repeat sequences, and 37,207 protein-coding genes were predicted. This genome assembly sets the stage for comparative genomic analysis of the diversification and adaptation of grapevine and will provide a solid resource for further genetic analysis and breeding of this economically important species. Footnotes * https://figshare.com/s/0a52d4408214e9f1e280 * https://www.ncbi.nlm.nih.gov/assembly/GCA_004353265.1 * https://www.ncbi.nlm.nih.gov/bioproject/PRJNA512170